Penerapan Restorative Justice Terkait dengan Over Capacity Lapas IIA Magelang (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Overcapacity in Correctional Institutions is a structural problem that is still a serious challenge in the correctional system in Indonesia. This condition is characterized by the number of inmates that far exceeds the ideal capacity, resulting in a decrease in the quality of coaching, health services, and security. This study aims to analyze the factors that cause overcapacity in prisons and the impact they have on the effectiveness of the correctional system. The method used is a normative juridical approach supported by empirical data from relevant agency reports. The results of the study show that the main factors causing overcapacity include the high crime rate, criminal policies that are still oriented towards prison sentences, and limited correctional facilities and infrastructure. The impact of overcapacity is very felt in the implementation of inmate development. Crowded housing conditions also increase conflicts between inmates, the spread of infectious diseases, and violations of basic rights. In addition, the limited number of correctional officers causes supervision to not run optimally and has the potential to trigger deviant practices in prisons. Therefore, it is necessary to reformulate penal policies through the optimization of non-prison penal alternatives, institutional capacity building, and strengthening rehabilitation and social reintegration programs to realize a more humane and just correctional system.